HHV8(+) EBV(+) Extracavitary/solid variant of primary effusion lymphoma in a HIV-negative and nonimmunosuppressed patient. - Güler, Beril; GÜLER, BERIL; Çetin, Güven; ÇETİN, GÜVEN (My University, 2021)
Additional test needed: PET/CT: Several hypermetabolic lymph nodes, approximately 1.5 cm in diameter, were observed at the subcarinal level (SUVmax: 12,7). A hypermetabolic mass/multiple lymphadenopathies with a conglomerate appearance of approximately 10 cm in diameter was detected in the periportal, peripancreatic and paracaval areas (SUVmax:18.3). No effusion was detected on imagings. ALT: 760 U/L, AST: 410 U/L, ALP: 838 U/L, GGT: 1055 U/L, Total Bilirubin: 5,6 mg/dL, Direct Bilirubin: 3,7 mg/dL, WBC: 12400 cells/uL, Neutrophil: %80,43-9680, Lymphocyte: %11,49-1380.Points to discuss at the panel meeting: Virally associated lymphoproliferative disorders have a broad spectrum and can present different clinical features. Actual rates of these lymphoma group may be higher than currently reported. They should also be considered in the differential diagnosis in cases without a history of immunosuppression or HIV enfection. HHV8 and EBV related lymphomas should be kept in mind especially in null cell phenotype lymphomas.Case description: Previously healthy, 50-year-old HIV(-) male patient who was hospitalized due to right upper quadrant pain, vomiting and icterus. No systemic B-symptoms were present. There was no history of malignancy, drug use, hepatitis B or hepatitis C infection or other causes of immunosuppression.Biopsy fixation details: Pancreatic head and celiac lymph node EUS/FNA; 4 alcohol fixed, 3 air-dried smears, 2 cell block materials. Duodenal endoscopic biopsy and portal hilar mass CNB: 10% neutral buffered formalinFrozen tissue available: -Details of microscopic findings: EUS guided FNA: The smears were moderately to highly cellular in the necrotic background. Discohesive, scattered atypical cells had medium- to large-sized round nuclei, coarce chromatin, single or several small nucleoli. Some of the cells are in the form of naked nuclei, some of them have a moderate amount of basophilic cytoplasm and plasmacytoid morphology. Mitotic figures are frequent, especially in cell block sections.Duodenal endoscopic biopsy: A diffuse proliferation of atypical cells that effaced the normal architecture and ulcerated surface was observed at the hematoxylin eosin sections. Atypical cells are large with round-to oval or lobulated nuclei, coarce chromatin, single or several prominent nucleoli and moderate amount eosinophilic or clear cytoplasma. In some areas plasmacytoid morphology was predominant. Mitosis was common.Portal hilar mass CNB: Core biopsy specimen was completely infiltrated with atypical cells. Atypical cells had similar morphological features to those observed in other biopsies.Immunophenotype: Positive: LCA, EMA, HHV-8, MUM1, IgM, CD38 (duodenum-, portal hilus weak+). Ki67 (%80-85).Negative: CD138, CD30, CD79a, CD20, Pax-5, CD3, CD4, CD8, CD2, CD5, CD7, CD43, CD56, CD10, Bcl6, CD34, CD117, MPO, CD99, ALK, CD68, CD33, CD1a, CD11c, CD123, CD163, CD21, CD15, S100, CD61, Glicophorin A, Kappa, Lambda, Pancytokeratin, Oscar-keratin, Chromogranin a, Synaptophysin, CEA, Desmin, Myogenin, MyoD1, HMB45, CD31. Oct2 (suboptimal reaction).Cytogenetics: -Molecular studies: EBER(+)Proposed diagnosis: HHV8(+), EBV(+) Extracavitary/solid variant of primary effusion lymphoma.Interesting feature(s) of submitted case: Disease has been presented with icterus and cholestasis. There was no history of malignancy, drug use, HIV, hepatitis B or hepatitis C infection or other causes of immunosuppression. The serous effusion was not detected in the patient. The case was diagnosed by duodenal endoscopic biopsy. Atypical lymphocytes had a null cell phenotype and were positive for both EBV and HHV8.
Keywords: Güler B., Çetin G., -HHV8(+) EBV(+) Extracavitary/solid variant of primary effusion lymphoma in a HIV-negative and nonimmunosuppressed patient.-, 20th MEETING OF THE EUROPEAN ASSOCIATION FOR HAEMATOPATHOLOGY, Dubrovnik, Hırvatistan, 25 - 29 Nisan 2021, ss.296